ChemInform Abstract: Recent Advances in Transition Metal‐Catalyzed Hydroacylation of Alkenes and Alkynes. Issue 26 (June 2016) - Ghosh, Avipsa; Johnson, Kirsten F.; Vickerman, Kevin L.; Walker, James A. Jr.; Stanley, Levi M.
Abstract: Review: 41 refs.